TRANSMISSION, RELATIONALITY, ETHNOGRAPHY. Issue 3 (4th May 2019) - Frosh, Stephen; Sheldon, Ruth
Abstract: The "relational turn" in social research raises many issues that might loosely be collected together under the heading of "reflexivity." This can have a variety of meanings, but here, following a newly articulated "tradition" in psychosocial studies, we are using it to think about how the relationality of the research process impacts upon, and is in turn influenced by, the relationality that is the subject of the research itself. We are interested in what we can discover about the research we might be engaged in through opening ourselves up to the relational context in which this research takes place. We suggest that attending closely to what happens between members of a research team can provide powerful insights into the substantive content of the research itself, helping create a more nuanced set of understandings than might otherwise have been possible. In this paper, we present material about the relationship that evolved between us whilst carrying out an ethnographic study of a London Jewish community. This material reveals a relationality that bears strongly on the content of the ethnography itself, specifically referring to intergenerational transmission and rupture, gender dynamics, and the problematics of vulnerability and loss.